Appropriation, Absence and the Canadian Studies Classroom. Issue 2 (3rd April 2019) - Blake, Jason
ABSTRACT: This article focuses on "appropriation of voice" or "cultural appropriation" in the Canadian Studies classroom. It is aimed at instructors who teach Canadian Literature outside Canada, in places where Canada is itself a strange, foreign or even exotic country. Keeping classroom practice in mind, I divide the article into three sections. The first provides a classroom-oriented overview of appropriation debates; the second looks at tokenism on reading lists; the third reflects on problems of absence or of dealing with canonical texts that skim over Canada's Indigenous Peoples — specifically, by analyzing two brief examples from Stephen Leacock's Sunshine Sketches of a Little Town (1912) and one from Anne Michaels's Fugitive Pieces (1996).